Polymeric microspheres/cells/extracellular matrix constructs produced by auto-assembly for bone modular tissue engineering - Mielan, B (2021)
Modular tissue engineering (MTE) is a novel “bottom-up” approach to create engineered biological tissues from microscale repeating units. Our aim was to obtain microtissue constructs, based on polymer microspheres (MSs) populated with cells, which can be further assembled into larger tissue blocks and used in bone MTE. Poly(L-lactide-co-glycolide) MS of 165 ± 47 µm in diameter were produced by oil-in-water emulsification and treated with 0.1 M NaOH. To improve cell adhesion, MSs were coated with poly-L-lysine (PLL) or human recombinant collagen type I (COL). The presence of oxygenated functionalities and PLL/COL coating on MS was confirmed by X-ray photoelectron spectroscopy (XPS). To assess the influence of medium composition on adhesion, proliferation, and osteogenic differentiation, preosteoblast MC3T3-E1 cells were cultured on MS in minimal essential medium (MEM) and osteogenic differentiation medium (OSG). Moreover, to assess the potential osteoblast–osteoclast cross-talk phenomenon and the influence of signaling molecules released by osteoclasts on osteoblast cell culture, a medium obtained from osteoclast culture (OSC) was also used. To impel the cells to adhere and grow on the MS, anti-adhesive cell culture plates were utilized. The results show that MS coated with PLL and COL significantly favor the adhesion and growth of MC3T3-E1 cells on days 1 and 7, respectively, in all experimental conditions tested. On day 7, three-dimensional MS/cell/extracellular matrix constructs were created owing to auto-assembly. The cells grown in such constructs exhibited high activity of early osteogenic differentiation marker, namely, alkaline phosphatase. Superior cell growth on PLL-and COL-coated MS on day 14 was observed in the OSG medium. Interestingly, deposition of extracellular matrix and its mineralization was particularly enhanced on COL-coated MS in OSG medium on day 14. In our study, we developed a method of spontaneous formation of organoid-like MS-based cell/ECM constructs with a few millimeters in size. Such constructs may be regarded as building blocks in bone MTE.